Evaluation of the Biocompatibility of New Fiber-Reinforced Composite Materials for Craniofacial Bone Reconstruction. Issue 7 (October 2016) - Lazar, Mădălina-Anca; Rotaru, Horaţiu; Bâldea, Ioana; Boşca, Adina B.; Berce, Cristian P.; Prejmerean, Cristina; Prodan, Doina; Câmpian, Radu S.
Abstract : Abstract: This study aims to assess the biocompatibility of new advanced fiber-reinforced composites (FRC) to be used for custom-made cranial implants. Four new formulations of FRC were obtained using polymeric matrices (combinations of monomers bisphenol A glycidylmethacrylate [bis-GMA], urethane dimethacrylate [UDMA], triethylene glycol dimethacrylate [TEGDMA], hydroxyethyl methacrylate [HEMA]) and E-glass fibers (300 g/mp). Every FRC contains 65% E-glass and 35% polymeric matrix. Composition of polymeric matrices are: bis-GMA (21%), TEGDMA (14%) for FRC1; bis-GMA (21%), HEMA (14%) for FRC2; bis-GMA (3.5%), UDMA (21%), TEGDMA (10.5%) for FRC3, and bis-GMA (3.5%), UDMA (21%), HEMA (10.5%) for FRC4. Cytotoxicity test was performed on both human dental pulp stem cells and dermal fibroblasts. Viability was assessed by tetrazolium dye colorimetric assay. Subcutaneous implantation test was carried out on 40 male Wistar rats, randomly divided into 4 groups, according to the FRC tested. Each group received subcutaneous dorsal implants. After 30 days, intensity of the inflammatory reaction, tissue repair status, and presence of the capsule were the main criteria assessed. Both cell populations showed no signs of cytotoxicity following the FRC exposures. In terms of cytotoxicity, the best results were obtained by FRC3 followed by FRC2, FRC4, and FRC1. FRC3 showed also the mildest inflammatory reaction and this correlated both with the noncytotoxic behavior and the presence of a well-organized capsule. The composite biomaterials developed may constitute an optimized alternative of the similar materials used for the reconstruction of craniofacial bone defects. According to authors' studies, the authors conclude that FRC3 is the best formulation regarding the biological behavior.